What Differences Make a Difference? - Parens, Erik (Cambridge quarterly of healthcare ethics, 1998)
Four years ago The Hastings Center initiated a “pluralism project.” That project gave the Center staff a chance to explore one swath of the theoretical literature concerning how members of democratic regimes ought to think about and respond to the differences among themselves. Much of that literature, produced by philosophers like Charles Taylor, Martha Nussbaum, and John Kekes, is wonderfully articulate about difference in general. But it is nearly silent about how particular categories of difference actually make a difference in the lives of particular individuals negotiating particular institutions.